Experimental Study on the Working Characteristics of a Pre-combustion AC Plasma Jet Igniter - Cheng, Weida; Yu, Jinlu; Jiang, Luyun; Miao, Qinyu; Zhang, Lei; Zhao, Bingbing (Frontiers in Energy Research, 2022)
A new pre-combustion AC plasma jet igniter has been designed. The pre-combustion plasma jet igniter can widen the ignition envelope for the aeroengine and reduce the power consumption of the igniter. To fully exploit the ignition efficiency of the plasma jet, experimental studies concerning the operational parameters and the discharge and arc motion characteristics have been performed. The results showed that three discharge modes were formed in the new igniter, namely, the Intermittent Breakdown Mode (IBM), the Stable Breakdown Mode (SBM) and the Stable-Intermittent Breakdown mode (S-IBM), the three different discharge modes corresponding to different arc shapes and movement processes. Moreover, the addition of kerosene readily changed the discharge state from the SBM to the IBM. The discharge state and discharge power of the igniter were affected by the working parameters. The discharge power increased with increase of the output voltage of the regulator, and an increase in the air supply affected the discharge power when the output voltage of the regulator was varied. After the addition of kerosene, the discharge power of the igniter was reduced to a certain extent, the maximum reduction being up to 47.7%.